VISUALISASI GEDUNG STMIK BANDUNG UNTUK PENGENALAN MAHASISWA BARU BERBASISAUGMENTED REALITY (AR) CONTROL DAN VIRTUAL REALITY (VR) - Mina Ismu Rahayu; Faiqunisa; Robby Herdiyansah (LPPM STMIK Bandung, 2021)
STMIK Bandung campus features various rooms, including classrooms, faculty offices, computer labs, and other facilities. Currently, room navigation relies on information displayed on campus walls or by asking staff, campus employees, and other students. A new application has been developed to visualize the STMIK Bandung building in the form of three-dimensional (3D) objects, serving as a medium to convey campus environment information through a building layout using AR (Augmented Reality) FPS (Control) and VR (Virtual Reality) technology. This application facilitates prospective students in obtaining information about the buildings on the STMIK Bandung campus. The software development methodology used is the waterfall method to address issues that arise during the creation of the AR FPS (Control) and VR application. The system design utilizes UML (Unified Modeling Language). The application is built using markerless techniques, a joystick, and virtual buttons. The tools used include Unity3D as the editor and Blender for designing the three-dimensional (3D) models.